Knowledge management strategies for capitalising on school knowledge. Issue 1 (13th February 2017) - Cheng, Eric C.K.
Abstract : Purpose: This paper aims to explore the extent to which knowledge management practices, that is the process of developing and sharing organisational knowledge, can enhance intellectual capital (IC) in the context of school education. Design/methodology/approach: A mixed-method approach was adopted as the research strategy. A cross-sectional quantitative survey was conducted to collect data from 445 teachers at 13 primary schools in Hong Kong. A structural equation model (SEM) was applied to confirm the predictive effective of knowledge strategies on school IC. Interviews were conducted in a case school to explore the process for capitalising the knowledge by Lesson Study. Findings: The result of the SEM shows that personalisation and codification strategies are predictors of human capital and structural capital at schools. The findings from interviews with the principals and teachers show that personalisation and codification strategies could be put into operation as a Lesson Study to leverage knowledge for school development. Originality/value: This paper contributes to the management practices of school organisation for enhancing their IC by conducting Lesson Study for the development of their schools effectively.